Real-Time Displacement and Strain Mappings of Lithium-Ion Batteries Using Three-Dimensional Digital Image Correlation - P. K., Leung; C., Moreno; I., Masters; S., Hazra; B., Conde; Mohd Rusllim, Mohamed; R. J., Dashwood; R., Bhagat (Elsevier Ltd, 2014)
This work presents the first application of three-dimensional digital image correlation for real-time displacement and strain analysis of a pouch type lithium-ion battery. During the electrochemical charge–discharge processes, displacements in the x-, y- and z-directions vary at different states-of-charge (SOCs) attributed to the expansion and the contraction of the interior structure. The z-displacement is observed to develop and concentrate at the vicinity of the openings of the jelly-roll structure. By resolving the displacement components, the progression and distribution of the surface strains, including principal and von-Mises strains, are computed in the charge–discharge processes. It is shown that the dominant strains are up to 0.12% in the rolling direction of the jelly-roll structure and distribute uniformly on the x–y plane over the surface.